Pengaruh Nilai Informatif, Nilai Hiburan, Keaslian, dan Homophily Terhadap Kredibilitas Merek dan Niat Beli yang di Mediasi Hubungan Parasosial - Fayestika Anantasia Pratiwi; Rini Kuswati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the impact of informative value, entertainment value, authenticity, and homophily on brand credibility and purchase intention mediated by parasocial relationships in digital marketing by social media influencers. The method used is Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships between variables. The study's population consists of active social media users following influencers, with a sample of 155 respondents. The results show that informative value, authenticity, and homophily significantly influence parasocial relationships, which in turn affect brand credibility and purchase intention. Entertainment value does not have a significant effect on parasocial relationships or purchase intention. Parasocial relationships mediate the effect of informative value, authenticity, and homophily on brand credibility and purchase intention, but not for entertainment value. This study provides insights for marketers in selecting the right influencer based on informative value, authenticity, and similarity in characteristics with the target audience.